Disrupted mitochondrial morphology and function exacerbate inflammation in elderly-onset ulcerative colitis - Mengmeng Zhang; Hong Lv; Xiaoyin Bai; Gechong Ruan; Qing Li; Kai Lin; Hong Yang; Jiaming Qian (Immunity & Ageing)
Abstract Background The characteristics of ulcerative colitis (UC) in the elderly are quite different from the young population. Mitochondrial injury is a key mechanism regulating both aging and inflammation. This study aims to reveal the role of mitochondrial damage in the pathogenesis of adult- and elderly-onset UC. Methods RNA-sequencing of colonic mucosa from adult- and elderly-onset UC patients was performed. Mitochondria-related differentially expressive genes (mDEGs) and immune cell infiltration analysis were identified and performed in colonic tissues from UC patients. Mice aged 6–8 weeks and 20–24 months were administered 2% dextran sodium sulphate (DSS) for 7 days to induce colitis. Mitochondrial morphological changes and ATP levels were evaluated in the colons of mice. Mechanistically, we explored the association of key mDEG with reactive oxygen species (ROS), oxygen consumption rates, NLRP3/IL-1β pathway in HCT116 cell line. Results Thirty mDEGs were identified between adult- and elderly-onset UC, which were related primarily to mitochondrial respiratory function and also had significant correlation with different infiltrates of immune cells. Compared with young colitis mice, DSS-induced colitis in the aged mice exhibited more severe inflammation, damaged mitochondrial structure and lower ATP levels in colonic tissues. ALDH1L1 was identified as a hub DEG through protein–protein interaction networks of RNA-seq, which was downregulated in UC patients or colitis mice versus healthy controls. In tumor necrosis factor-alpha-stimulated HCT116 cells, mitochondrial ROS, NLRP3 and IL-1β expression increased less and mitochondrial respiration had an upregulated trend after knocking down ALDH1L1. Conclusion There are significant differences in mitochondrial structure, ATP production and mitochondria-related gene expression between adult- and elderly-onset UC, which have a potential link with cytokine pathways and immune microenvironment. The more prominent mitochondrial injury may be a key factor for more severe inflammatory response and poorer outcome in elderly-onset UC.